Investigation of Magnetic, Electrical and Optical Properties of Soft-Hard Ferrite Composite Synthesized by Sol-Gel Technique. Issue 1 (12th February 2023) - Ganesh, K.; Pavan Kumar, N.; Sambasiva Rao, K.; Lalitha, G.
Abstract: Soft and hard composites of ferrites with compositional formula (NiFe2 O4 )100-x – (BaFe12 O19 )x (where x  = 0, 20, 50, 60, 80, 100) were prepared using sol-gel method. The samples were calcined individually at 900 °C and composites in the required proportions were sintered at 1100 °C in a conventional furnace. The coexistence of NiFe2 O4 and BaFe12 O19 composites has been confirmed by the X-ray diffraction studies and found to be without any impurities. Rietveld analysis of X-ray diffractograms corroborates hexagonal phase with P63/mmc space group for Barium hexaferrite and cubic phase with Fd-3m:2 space group for Nickle ferrite. The surface morphology was investigated by scanning electron microscopy (SEM), and the micrographs are observed to indicate well distributed grains in the exchange coupled composites. Grains of nano-size about 100–300 nm are formed for the composites. The magnetic properties have been studied by VSM and electric properties were studied by measuring the dielectric constant at room temperature. UV; FTIR studies of the samples are exhibiting fundamental absorption bands.